RECONSTRUCTION OF A DESIGN THINKING-BASED MORAL EDUCATION LEARNING MODEL FOR GENERATION Z: A LITERATURE REVIEW STUDY - Muslem Muslem (Jurnal Ikhtibar Nusantara, 2026)
This integrative literature review aims to reconstruct a Design Thinking (DT)-based learning model for moral education (akhlak) tailored to Generation Z in the digital age. The study systematically analyses 25 primary sources (scientific journals, proceedings, dissertations) published between 2016 and 2025. The findings reveal a significant gap between conventional normative teaching methods and the characteristics of Gen Z as digital natives, requiring a contextual and participatory learning paradigm. The analysis identifies Design Thinking as a powerful and philosophically aligned solution. DT’s human-centered, iterative stages (Empathize, Define, Ideate, Prototype, Test) show deep convergence with Islamic moral concepts, such as at-ta'āthuf (compassion) and at-tajribah (experimentation). The synthesis results in a proposed conceptual model that integrates the DT mindset, Gen Z’s digital-native traits, and the objectives of Islamic moral education. The reconstructed model shifts learning from passive transmission to an active, experiential process where students explore real-world moral dilemmas, collaboratively prototype behavioral solutions, and engage in continuous reflection. This study provides a theoretical foundation and operational framework for educators and curriculum developers to design more relevant, impactful, and adaptive moral education for the 21st century.